Glucocorticoid receptor activity regulates light adaptation in the zebrafish retina - Muto, Akira; Taylor, Michael R.; Suzawa, Miyuki; Korenbrot, Juan I.; Baier, Herwig (Frontiers in Neural Circuits, 2013)
Glucocorticoids modulate diverse aspects of physiology and behavior, including energy homeostasis, stress response, and memory, through activation of the glucocorticoid receptor (GR). Light perception has profound effects on the production of glucocorticoids via functional connections of the retina to the hypothalamus-pituitary-adrenal (HPA) axis. We report here that glucocorticoids can also signal in the reverse direction, i. e., regulate visual function in zebrafish, Danio rerio. The zebrafish GR mutant, grs357, harbors a missense mutation that completely blocks the transcriptional activity of GR. In this mutant, visual behavior was abolished following a period of darkness and recovered sluggishly after return to the light. Electrophysiological measurements showed that the photoresponse of the dark-adapted retina was reduced in the mutant and re-adapted to light with a substantial delay. Several gene products, including some that are important for dopaminergic signaling, were misregulated in grs357 mutants. We suggest that GR controls a gene network required for visual adaptation in the zebrafish retina and potentially integrates neuroendocrine and sensory responses to environmental changes.